Investigation of an erasing method for synaptic behaviour in a phase change device using Ge1Cu2Te3 (GCT). Issue 18 (1st September 2016) - An, J.S.; Choi, C.M.; Shindo, Y.; Sutou, Y.; Jeong, H.S.; Song, Y.H.
Abstract : The gradual erasing operation from reset state to set state adjusting pulse amplitude, duration time and falling time respectively in phase change device using Ge1 Cu2 Te3 is investigated. For this procedure, a relatively high voltage and increased falling time, which was able to produce both long‐term potential and long‐term depression in the time interval between pre‐spike and post‐spike is choosing. The results suggested that the presence of synaptic behaviour was due to controlled falling time rather than pulse amplitude.